2017
DOI: 10.1016/j.bbmt.2017.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Defibrotide in the Prophylaxis of Veno-Occlusive Disease after Pediatric Allogeneic Stem Cell Transplantation

Abstract: Veno-occlusive disease (VOD) remains a serious complication after allogeneic hematopoietic stem cell transplantation (HSCT). Prophylactic use of defibrotide (DF) might further reduce VOD rates but has no impact on the incidence of severe VOD or VOD-associated mortality. We investigated the cost-effectiveness of prophylactic DF according to the British Committee for Standards in Haematology/British Society for Blood and Marrow Transplantation guidelines in 348 children who underwent transplantation between 2001… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
(46 reference statements)
0
10
0
Order By: Relevance
“…Though previous studies 6,9 using DF prophylaxis for longer periods than us have shown protective effect, most of them have included allogeneic 6 or both allogeneic and autologous transplant patients 9 . It is unclear if extending the duration of DF prophylaxis (beyond day +14) would have been helpful in our cohort, but it would have surely led to significant escalation of cost 26 …”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Though previous studies 6,9 using DF prophylaxis for longer periods than us have shown protective effect, most of them have included allogeneic 6 or both allogeneic and autologous transplant patients 9 . It is unclear if extending the duration of DF prophylaxis (beyond day +14) would have been helpful in our cohort, but it would have surely led to significant escalation of cost 26 …”
Section: Discussionmentioning
confidence: 96%
“…UDCA is an inexpensive and safe intervention as compared with DF, which is costly and has been associated with potentially hazardous adverse effects such as bleeding. A recent paper on the prophylactic use of DF in children undergoing allogenic stem cell transplant has not shown DF to be a cost‐effective intervention either 26 …”
Section: Discussionmentioning
confidence: 99%
“…45 Recently, a cost-effectiveness analysis of defibrotide prophylaxis was conducted in 348 children undergoing HCT. 46 The incidence of VOD in the cohort was 7.4%. Risk factors for VOD/SOS were present in 39.6% of patients, and the incidence of VOD/SOS was significantly greater in patients with risk factors when compared with those without (15.2% vs 2.4%, P < 0.0001).…”
Section: Availability and Cost Considerationsmentioning
confidence: 86%
“…13 Although there are efficacy data to support this strategy, cost-effectiveness data do not support the use of defibrotide prophylaxis in all patients receiving HCT. 46 Additionally, the optimal dose, timing, and duration for prophylaxis have yet to be established. A phase 3 study of defibrotide compared with best supportive care for VOD/ SOS prevention in adult and pediatric patients is currently recruiting, with a planned primary outcome of VOD-free survival at day +30 and secondary outcome of VOD-free survival at day +100 post-HCT.…”
Section: Place In Therapymentioning
confidence: 99%
“…In addition, several studies have examined DF prophylaxis can reduce the incidence of VOD/SOS in high-risk patients. [12][13][14][15] With this study, we report our experience with the prophylactic use of DF in pediatric HSCT recipients who were considered at high-risk for VOD/ SOS.…”
mentioning
confidence: 99%